Acetylcholine receptors in water. Issue 4 (3rd April 2018) - Bibal, Brigitte
Abstract: This review focuses on the recognition and the detection of the acetylcholine neurotransmitter by artificial receptors, in water and buffered water. The design of water-soluble hosts and the advanced devices based on this (host:ACh) chemistry are also presented. Abstract :